Anellovirus loads are associated with outcomes in pediatric lung transplantation. (29th October 2017) - Blatter, Joshua A.; Sweet, Stuart C.; Conrad, Carol; Danziger‐Isakov, Lara A.; Faro, Albert; Goldfarb, Samuel B.; Hayes, Don; Melicoff, Ernestina; Schecter, Marc; Storch, Gregory; Visner, Gary A.; Williams, Nikki M.; et al.
Abstract: Anelloviruses are DNA viruses ubiquitously present in human blood. Due to their elevated levels in immunosuppressed patients, anellovirus levels have been proposed as a marker of immune status. We hypothesized that low anellovirus levels, reflecting relative immunocompetence, would be associated with adverse outcomes in pediatric lung transplantation. We assayed blood samples from 57 patients in a multicenter study for alpha‐ and betatorquevirus, two anellovirus genera. The primary short‐term outcome of interest was acute rejection, and longer‐term outcomes were analyzed individually and as "composite" (death, chronic rejection, or retransplant within 2 years). Patients with low alphatorquevirus levels at 2 weeks post‐transplantation were more likely to develop acute rejection within 3 months after transplant ( P  = .013). Low betatorquevirus levels at 6 weeks and 6 months after transplant were associated with death ( P  = .047) and the composite outcome ( P  = .017), respectively. There was an association between low anellovirus levels and adverse outcomes in pediatric lung transplantation. Alphatorquevirus levels were associated with short‐term outcomes (ie, acute rejection), while betatorquevirus levels were associated with longer‐term outcomes (ie, death, or composite outcome within 2 years). These observations suggest that anelloviruses may serve as useful biomarkers of immune status and predictors of adverse outcomes.